Pembuatan Chocolate Steamed Cake Dengan Subtitusi Tepung Sukun Guna Pemanfaatan Pangan Lokal - Anggraeni Stj, Rr. Christiana Mayang; Ayuasih, Anisa Vitri (Universitas Sarjanawiyata Tamansiswa, 2024)
This research aimed to (1) Obtain a chocolate steamed cake formulation with the substitution of breadfruit flour, (2) Know the level of acceptance of chocolate steamed cake with breadfruit flour substitute, (3). Find out the percentage of breadfruit flour that produces the best chocolate steamed cake. This research uses an experimental method using hedonic tests. The hedonic test was carried out with a total of 25 panelists. The formulation used in this research was 100% wheat flour as a control, 25% breadfruit flour, 50% breadfruit flour, and 75% breadfruit flour. The results of this research, namely the 25% breadfruit flour formulation, received the superior score compared to other formulations with a sample mean score of 4.2 out of 5 and overall acceptability of 84%, which was a product category favored by the panelists.